2000
DOI: 10.1046/j.1442-2018.2000.00036.x
|View full text |Cite
|
Sign up to set email alerts
|

Day surgery patients' convalescence at home: Does enhanced discharge education make a difference?

Abstract: The day surgery concept has been adopted and used widely. To date, there is limited in‐depth research that has reviewed patients' experiences convalescing from day surgery and the degree to which community, medical, allied health and social assistance is required. In addition, research indicates that day surgery patients' educational preparedness may influence patients' abilities to better self‐manage their postoperative recovery. Using a simple interrupted time series design, this study evaluated and compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
30
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 11 publications
1
30
0
Order By: Relevance
“…Day surgery implies a short period of surveillance at the surgery unit before home discharge. After leaving the surgery unit, patients have to manage postoperative problems on their own together with their personal network [2,3]. Despite this, day surgery is a preferred and desired choice for most patients as it offers an efficient service with minimal disruption of personal habits and routines [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Day surgery implies a short period of surveillance at the surgery unit before home discharge. After leaving the surgery unit, patients have to manage postoperative problems on their own together with their personal network [2,3]. Despite this, day surgery is a preferred and desired choice for most patients as it offers an efficient service with minimal disruption of personal habits and routines [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Readmission to the hospital may occur, with persistent pain mentioned as a common cause. 26,27 The purpose of this study was to determine if postoperative pain level was associated with demographic or surgery-specific characteristics in a sample of 248 participants recovering from ambulatory surgery; and to assess the relationship between high pain and nausea over the 7-day postoperative period in this group, controlling for demographic and surgery-specific covariates. It was hypothesized that high pain would be associated with demographics and surgeryrelated variables, and that degree of pain would be related to nausea over time, even when controlling for personal and surgical variables.…”
mentioning
confidence: 99%
“…A number of studies have suggested carer responsibility is likely to increase with the rise in day surgery (Swan et al 1998, Young et al 2000, Erkal 2007. Berg et al (2011) stated patients can take two weeks to recover and require much carer support than suggested during consultation.…”
Section: Introductionmentioning
confidence: 99%